Investing in Nature as the true engine of our economy: A 10-point Action Plan for a Circular Bioeconomy of Wellbeing - Palahí, M.; Pantsar, M.; Costanza, R.; Kubiszewski, I.; Potočnik, J.; Stuchtey, M.; Nasi, R.; Lovins, H.; Giovannini, E.; Fioramonti, L.; Dixson-Declève, S.; McGlade, J.; et al. (European Forest Institute, 2020)
The 10-Point Action Plan to catalyse a Circular Bioeconomy of Wellbeing is a call for collective and integrated action to global leaders, investors, companies, scientists, governments, nongovernmental and intergovernmental organisations, funding agencies and society at large to put the world on a sustainable path.